2022
DOI: 10.1155/2022/3523920
|View full text |Cite
|
Sign up to set email alerts
|

Antimycotic Activity of Some Medicinal Plants against Mucor circinelloides

Abstract: The in vitro antimycotic activity of the leaf extract of Catharanthus roseus, Lantana camara, Nerium indicum, Sida cordifolia, and Ziziphus mauritiana was studied against M. circinelloides. This fungal species causes mucormycosis (black fungus). Presently, mucormycosis is affecting COVID patients due to prolonged use of steroids. So, it is needed to require development of more effective and less toxic antimycotic agents for the treatment of mucormycosis. Plants and their extraction preparations have been used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Dermatophytes are keratinophilic fungi closely related to a unique group of organisms, mostly composed of 3 main genera, including Trichophyton, Microsporum, and Epidermophyton that infect keratinous tissue (nails, hairs, and skin) of live human hosts, and other animals to produce infection [60]. In line with our results, Jangid and Begum [61] stated that dermatophytes are fungal pathogens of animals and humans that infect the keratinized tissues, e.g., nails, hairs, and skin, since they produce several kinds of virulence factors for infection, such as keratinase, sulfite, exoprotease, and endoprotease to penetrate into the stratum corneum of the host tissues and produce disease. Shanmuga et al [62] reported that the hemolytic factor plays a vital role in dermatophytic infections because of the cytotoxic effects on RBC and phagocytic cells, which results in the formation of pores and lysis.…”
Section: Discussionsupporting
confidence: 87%
“…Dermatophytes are keratinophilic fungi closely related to a unique group of organisms, mostly composed of 3 main genera, including Trichophyton, Microsporum, and Epidermophyton that infect keratinous tissue (nails, hairs, and skin) of live human hosts, and other animals to produce infection [60]. In line with our results, Jangid and Begum [61] stated that dermatophytes are fungal pathogens of animals and humans that infect the keratinized tissues, e.g., nails, hairs, and skin, since they produce several kinds of virulence factors for infection, such as keratinase, sulfite, exoprotease, and endoprotease to penetrate into the stratum corneum of the host tissues and produce disease. Shanmuga et al [62] reported that the hemolytic factor plays a vital role in dermatophytic infections because of the cytotoxic effects on RBC and phagocytic cells, which results in the formation of pores and lysis.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, the use of various natural plant compounds to suppress the pathogenic organisms has evolved [ 8 , 110 ]. Plant products are important sources of therapeutic medications for infectious diseases, and they are reported to have little or no adverse effects when compared to synthetic drugs [ 113 ]. Fungal infections cause a wide range of disorders, including aspergillosis, candidiasis, dermatophytosis, and mucormycosis [ 113 ].…”
Section: Resultsmentioning
confidence: 99%
“…Plant products are important sources of therapeutic medications for infectious diseases, and they are reported to have little or no adverse effects when compared to synthetic drugs [ 113 ]. Fungal infections cause a wide range of disorders, including aspergillosis, candidiasis, dermatophytosis, and mucormycosis [ 113 ]. Plant extracts are frequently employed as a source of medicinal agents, mostly for antifungal purposes.…”
Section: Resultsmentioning
confidence: 99%
“…Efficacy of various medicinal plants has been studied against the causative fungus of mucormycosis. Antifungal activity of the Ethanolic leaf extracts of plants Ziziphus mauritiana Catharanthus roseus, Lantana camara, Nerium indicum, Sida cordifolia were studied against the fungus Mucor circinelloides using the disc diffusion assay.Results of this investigative study showed that ethanolic leaf extracts of C. roseus had high antimycotic activity against M. circinelloides while Z. mauritiana's leaf extracts exhibited minimum antifungal activity against M. circinelloides ( Bhadauria et al,2011;Renu et al,2022).…”
Section: Introductionmentioning
confidence: 99%